Effects of deposit facility rate on banks’ asset allocation in the Eurozone - Nguyen, Trang (2021)
As one of characteristics reflecting the exceptionally easing monetary policy of the ECB since the financial crisis of 2008, the deposit facility rate (DFR) was first pushed down to the zero-lower bound. Then, it entered the negative zone in June 2014. To investigate the pass-through of this policy rate to the banking markets, I use a data set of 19 eurozone countries from 2009-2019 to examine whether the DFR successfully lowers bank reserves, conditional on their business model being proxied by net interest margin and wholesale funding ratio. If bank reserves decline in response to the DFR reduction, it is important to reveal whether the banks use this additional liquidity for lending expansion or investments on higher-yield liquid assets. I find that banks withhold more reserves in response to a decrease of DFR and even behave more aggressively under the negative era after 2014, which is a plausible reaction under the high overall uncertainty, that has resulted from the negative interest rate policy and low-for-long period. Although bank lending has increased after 2014, it seems to have been caused more by unconventional tools other than the negative interest rate policy or main refinancing operations. Additionally, the country effect creates heterogeneity on loan supply changes as a response to the DFR change. Banks in the stressed countries generally have more incentives towards increasing lending, while banks in the non-stressed countries show a preference in liquidity withholding.